Der Schriftsteller und der Ort. Aussagen der DDR-Autoren zum Thema: „Mein Ort". Versuch einer textimmanenten Interpretation - Szubartowicz, Sławomira (Wydawnictwo Naukowe UAM, 1993)
The article is about the search of identity by the writers from the German Democratic Republic. The author analysed in it the prose forms of opinions of seven writers representing different generations in the German Democratic Republic (H. Richter, l. von Wangenheim, M. Neumann, O. Herbert, U. Püschel, B. Wogatzki and W. Kaufmann). These opinions appeared in April1986 in the East German literary journal "Neue Deutsche Literature". In all the utterances the autobiographical trend strikes us in which direction the authors go in order to picture the phenomenon of looking by them of the so called "one's own place" in the spiritual landscape of the divided Germany. The autobiographical record makes it possible for the above mentioned authors to present the problem of East German writer's identity in a measurable and concrete manner with reference to a given writer as human being thus making it possible for him to avoid the burden of historical motivation in relation to their own national history. Giving up the historical dimension of the problem of German identity the above mentioned writers resort to the geographical experience of the place of residence; to the neighbourly relations started on its basis; to the family tradition of customs in order to come from this externally experienced perspective of a given territory to the extra-territorial generalizations concerning the symbolic place of man on an equally symbolically understood earth. This kind of an all-compassing imagination of the above mentioned writers from the German Democratic Republic in their considerations on the subject of identity renders both their need of transgressing the tight territorial boundaries of their own statehood and is an example of an escape into utopia, sentimentalism and the myth of man with his brotherly, supranational earthly paradise. Thus the problem of identity of writers from the German Democratic Republic may, at least with reference to the above mentioned authors, be considered as controversial and unsolved.